What is the value of b^2 - 4ac for the following equation?
5x^2 + 7x = 6

The value of b^2 - 4ac for the following equation of 5x^2 + 7x = 6 is 169 . b^2 - 4ac = 7^2 - 4*5*(-6) = 49 + 120 = 169 .

s

Question

Asked 11/21/2014 10:15:51 PM

Updated 11/21/2014 11:21:29 PM

1 Answer/Comment

Rating

5

The value of b^2 - 4ac for the following equation of 5x^2 + 7x = 6 is 169 .

b^2 - 4ac = 7^2 - 4*5*(-6) = 49 + 120 = 169 .

b^2 - 4ac = 7^2 - 4*5*(-6) = 49 + 120 = 169 .

Added 11/21/2014 11:21:29 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/21/2014 11:33:08 PM]

Find the seventh term of the following sequence?
1.5, 3, 6, ...

Question

Not Answered

Updated 11/16/2014 11:44:11 PM

1 Answer/Comment

The seventh term of the following sequence: 1.5, 3, 6, is 96.

common ratio = 6/3 = 3/1.5 = 2

7th term = 1.5*2^(7 - 1) = 1.5*2^6 = 1.5*64 = 96

common ratio = 6/3 = 3/1.5 = 2

7th term = 1.5*2^(7 - 1) = 1.5*2^6 = 1.5*64 = 96

Added 11/16/2014 11:44:11 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/17/2014 12:26:17 AM]

Which of the following constants can be added to x^2 - 6x to form a perfect square trinomial? **Weegy:** The answer is 1/4.
Here, I'll show you how to get that answer:
Trial and Error Method:
1) 1/4, [ 1/2 and 1 are the possible answers in the choices but we know that 1/2 is not a perfect square so it's not possible for 1/2 to be the answer.
2) Now try 1/4 and 1 and add them to the equation to get:
x2 - x + 1/4
x2 - x + 1
3)Use the perfect square formula if you can:
x2 - x + 1/4 becomes (x-1/2)2? Yes!
x2 - x + 1 becomes (x-1)2?...No! that's wrong because (a-b)2 = a2-2ab +b2
Thus, 1/4 is the answer.
Easy Formula Method:
1) In a perfect square trinomial, c = (b/2a)2.
a=1 because it's the co-efficient of x2
b=1 because it's the coefficient of x
c=? and it's the missing constant
using the formula and the given, c = 1/4.
That's it! :D Good Luck!
] (More)

Question

Updated 12/4/2014 10:11:30 PM

1 Answer/Comment

9 can be added to x^2 - 6x to form a perfect square trinomial.

x^2 - 6x + 9 = (x - 3)^2

x^2 - 6x + 9 = (x - 3)^2

Added 12/4/2014 10:11:30 PM

This answer has been confirmed as correct and helpful.

Solve the following quadratic equation using the quadratic formula and then choose the correct solution set.
5x^2 + 7x = 6

Question

Updated 11/21/2014 11:24:30 PM

1 Answer/Comment

5x^2 + 7x = 6 ;

5x^2 + 7x - 6 = 0 ;

(5x - 3)(x + 2) = 0 ;

when 5x- 3 = 0 , x = 3/5 ;

when x + 2= 0 , x = -2 ;

The solution for 5x^2 + 7x = 6 is x = 3/5 , or x = -2.

5x^2 + 7x - 6 = 0 ;

(5x - 3)(x + 2) = 0 ;

when 5x- 3 = 0 , x = 3/5 ;

when x + 2= 0 , x = -2 ;

The solution for 5x^2 + 7x = 6 is x = 3/5 , or x = -2.

Added 11/21/2014 11:24:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/21/2014 11:28:41 PM]

Solve the following quadratic equation using the quadratic formula and then choose the correct solution set.
6x^2 - 7x + 2 = 0

Question

Updated 11/21/2014 11:19:55 PM

1 Answer/Comment

6x^2 - 7x + 2 = 0

(3x - 2)(2x - 1) = 0

3x - 2 = 0 ,x = 2/3

2x - 1 = 0, x = 1/2

The solution for 6x^2 - 7x + 2 = 0 is x = 2/3 , or x = 1/2 .

(3x - 2)(2x - 1) = 0

3x - 2 = 0 ,x = 2/3

2x - 1 = 0, x = 1/2

The solution for 6x^2 - 7x + 2 = 0 is x = 2/3 , or x = 1/2 .

Added 11/21/2014 11:19:55 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/22/2014 4:50:34 AM], Rated good by andrewpallarca

34,448,464

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 612 [Total 6485] Ratings 11 Comments 502 Invitations 0 Online

There are no comments.